Ecosystems of the Mediterranean Sea A Photographic Dive - Glaeser, Georg; Abed-Navandi, Daniel (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book invites snorkelers and divers on an educational visit to the most important ecosystems of the Mediterranean Sea. Keystone species from brown algae to dolphins are presented in their marine habitats and understood as part of a complex ecological system. Instead of grouping animals and plants taxonomically, we have organised them according to the eight main habitats of the Mediterranean Sea. Our journey starts with different types of rocky grounds, then takes you further to the Mediterranean's sandy and muddy grounds, and finally ends with the fish and dolphins of the blue open sea. You will be introduced to 220 ecologically significant animal and plant species via the texts of Daniel Abed-Navandi, a long-time lecturer on the biodiversity of the Mediterranean Sea at the University of Vienna, and the photographs of Georg Glaeser, the master behind the camera, who captures marine life on the spot.
Habitat: Sunlit Rocky Grounds -- Habitat: Shady Rocky Grounds -- Habitat: Dark Caves -- Habitat: Intertidal Zone -- Habitat: Sandy Grounds -- Habitat: Seagrass -- Habitat: Muddy Grounds -- Habitat: Open Waters -- Humans and the Sea.
Keywords: Freshwater ecology; Marine ecology; Biotic communities; Zoology; Biodiversity; Freshwater and Marine Ecology; Ecosystems; Zoology; Biodiversity